Laparoscopic partial splenectomy using the harmonic scalpel for parenchymal transection: two case reports and review of the literature - Di Mauro, Davide; Fasano, Angelica; Gelsomino, Mariannita; Manzelli, Antonio (Acta Biomedica Atenei Parmensis, 2021)
Laparoscopic splenectomy is nowadays widely performed for the treatment of benign and malignant diseases of the spleen. However, removing the spleen increases the risk of postoperative infections, therefore patients need long-life antibiotics. Advancement in surgical technique and instrumentation have led to the development of partial splenectomy, which is mainly indicated to treat localized lesions of the spleen. The main advantage is the preservation of the immune function, so that long-life prescription of antibiotics is no longer needed. The introduction of the laparoscopic approach to laparoscopic splenectomy seems to add further benefits, namely a faster recovery. We report two cases of benign splenic cysts, which were treated by laparoscopic partial splenectomy. Technical aspects on the parenchymal transection and data from the most recent literature are discussed as well.